Pacifying Asia, Orienting the Pacific: What Work Can a Life-Writing Region Do?. Issue 4 (2nd October 2017) - Howes, Craig
ABSTRACT: In 2008, Philippe Lejuene asked the non-rhetorical question 'Is the I International?' This paper explores what effect thinking about regions can have on our understanding of what links life-writing practices, and what may necessarily keep them apart. As the third designated area for the International Auto/Biography Association, preceded by IABA Europe and IABA Americas, IABA Asia/Pacific faces some especially difficult challenges in engaging productively with the largest, most geographically, culturally, linguistically, and historically diverse region so inscribed. After outlining these challenges, and offering a history of various attempts at theorising or representing the Asia/Pacific region as a site for life writing, I will offer some suggestions about focus, possible directions, and responsibilities for an initiative that will stimulate discussion and productive collaboration.